121k views
2 votes
I need to know the steps to solve the problem.

I need to know the steps to solve the problem.-example-1
User Tim Hunt
by
5.7k points

1 Answer

4 votes

Solution


\begin{gathered} y=-5x^2+x-1 \\ y=-7 \end{gathered}

Step 1: Substitute the value of y


\begin{gathered} y=-5x^2+x-1 \\ y=-7 \\ -7=-5x^2+x-1 \end{gathered}

Step 2: Collect the like terms:


\begin{gathered} -7=-5x^2+x-1 \\ 5x^2-x+1-7=0 \\ 5x^2-x-6=0 \\ 5x^2+5x-6x-6=0 \\ 5x(x+1)-6(x+1)=0 \\ (5x-6)(x+1)=0 \\ 5x-6=0,x+1=0 \\ 5x=6,x=-1 \\ x=(6)/(5),x=-1 \end{gathered}

Therefore the solution are:


\begin{gathered} x=-1,x=(6)/(5) \\ x=(-1,(6)/(5)) \end{gathered}

User Igor Konoplyanko
by
5.2k points